PERBEDAAN POLA KONSUMSI DAN STATUS GIZI ANTARA REMAJA DENGAN ORANG TUA DIABETES MELITUS (DM) DAN NON DM - Denov Marine; Sri Adiningsih (Media Gizi Indonesia, 2015)
Adolescents prefer to consume high fat and high sugar food compare to healthy food such as fruit and vegetable. High fat and high sugar food are risk factor of diabetes mellitus development, especially in adolescents whose parents had diabetes mellitus. The aim of this study was to analyze the difference of eating habit and nutritional status between adolescents with DM parents and non DM parents. This was a cross-sectional research included 42 adolescents as sample that divided into 21 adolescents with DM parents and 21 adolescents with non DM parents. The sample was chosen randomly using simple random sampling technique. The difference of each variable was analyzed using Independent T-test and Mann Whitney (α = 0,05). The result showed that there was no difference of high glycemic index food consumption (p = 0,229) and fruit – vegetable consumption (p = 0,14) between adolescents with DM parents and non DM parents. However, adolescents with DM parents were eat high GI food more often compared to adolescents with non DM parents. There was a difference of BMI (Body Mass Index) between adolescents with DM parents and non DM parents (p = 0,036). The research concludes that most of adolescents with DM parents were obese. The adolescents need to reduce the frequency of high glycemic index (GI) food consumption, increase fruits and vegetable consumption, and also increase physical activities, particularly for adolescent with DM parents.Keywords: Diabetes Mellitus, genetic factor, consumption patterns, nutritional status